Nanofiltration membrane and preparation method thereof

By generating a polymer active separation layer on the surface of a porous support membrane, the problems of low fluoride ion rejection rate and poor stability of existing nanofiltration membranes are solved, and a nanofiltration membrane with high efficiency in fluoride removal and stable operation is realized.

CN121198053APending Publication Date: 2025-12-26RINLAND ENVIRONMENT TECH (BEIJING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511368603.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-24
Publication Date
2025-12-26

AI Technical Summary

Technical Problem

Existing polymer nanofiltration membranes have low rejection rates for monovalent fluoride ions, resulting in a trade-off between separation and permeation performance. Furthermore, their poor operational stability and resistance to fouling limit their application in water defluorination.

Method used

A porous support membrane is impregnated with an aqueous dispersion of hydroxyapatite nanoparticles containing polyamine monomers and an organic solution of polyacrylamide monomers. Polymers are generated on the surface of the porous support membrane through the polymerization reaction of polyamine monomers and polyacrylamide monomers, forming an active separation layer and constructing a nanofiltration membrane with a nano-polyamide mixed matrix.

Benefits of technology

It improves the permeability and fluoride ion selectivity of nanofiltration membranes, significantly increases the fluoride ion rejection rate, and enhances the membrane's stability and antifouling properties, making it suitable for fluoride removal in water bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121198053A_ABST
    Figure CN121198053A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of membrane separation, in particular to a nanofiltration membrane and a preparation method thereof.The method comprises the steps that the surface of a porous supporting membrane is sequentially impregnated with a hydroxyapatite nanoparticle water-phase dispersion liquid containing a polyamine monomer and a polyacyl chloride monomer organic-phase solution; generating a polymer on the surface of the porous support membrane through a polymerization reaction of a polyamine monomer and a polyacyl chloride monomer; the polymer is used as an active separation layer, and the porous support membrane and the active separation layer are used as nanofiltration membranes. According to the invention, the nano polyamide mixed matrix nanofiltration membrane is generated on the porous support membrane through the polyamine monomer and the polyacyl chloride monomer. The hydroxyapatite nanoparticles and the polyamide matrix are combined through chemical bonds, so that the permeability and fluorine ion selectivity of the nanofiltration membrane are improved, and meanwhile, the membrane stability is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of membrane separation, in particular to a nanofiltration membrane and a preparation method thereof. BACKGROUND

[0002] At present, fluorine pollution in water bodies has become a global public health problem, so eliminating fluorine pollution in water bodies has become a technical problem to be solved urgently.

[0003] At present, the main technical means for eliminating fluorine pollution in water bodies is membrane separation technology. However, conventional polymer nanofiltration membranes have many shortcomings, for example, the monovalent fluorine ion rejection rate is not high, there is a trade-off effect between separation performance and permeation performance, that is, by narrowing the membrane pore size, the pore size screening effect is improved to increase the fluorine ion rejection, and the permeation flux will also be attenuated. In addition, the problems of relatively poor running stability and anti-pollution of the membrane limit its further application in the field of defluorination in water bodies. SUMMARY

[0004] The present application provides a nanofiltration membrane and a preparation method thereof, which are used to solve the problems of low fluorine ion rejection rate and poor running stability of the membrane.

[0005] In one embodiment, a preparation method of a nanofiltration membrane is provided, the method comprising: sequentially immersing the surface of a porous support membrane with a hydroxyapatite nanoparticle aqueous dispersion solution containing a polyamine monomer and a polyacyl chloride monomer organic phase solution, generating a polymer on the surface of the porous support membrane through a polymerization reaction of the polyamine monomer and the polyacyl chloride monomer; taking the polymer as an active separation layer, and taking the porous support membrane and the active separation layer as the nanofiltration membrane.

[0006] In one embodiment, the hydroxyapatite nanoparticle aqueous dispersion solution containing a polyamine monomer is obtained by: adding hydroxyapatite nanoparticles into water to obtain a hydroxyapatite nanoparticle aqueous solution by stirring; adding an anionic surfactant to the hydroxyapatite nanoparticle aqueous solution to obtain a solution after primary ultrasonic treatment by primary ultrasonic treatment; adding a polyamine monomer to the solution after primary ultrasonic treatment to obtain the hydroxyapatite nanoparticle aqueous dispersion solution after secondary ultrasonic treatment by secondary ultrasonic treatment.

[0007] In an embodiment, the anionic surfactant comprises at least one of sodium dodecyl sulfate, sodium dodecyl benzene sulfonate, sodium stearate, sodium polyvinyl alcohol sulfonate, sodium laurate; and / or the polyamine monomer comprises at least one of piperazine, m-phenylenediamine, N-aminoethyl piperazine, p-phenylenediamine; and / or the polyacyl chloride monomer in the organic phase solution of the polyacyl chloride monomer comprises at least one of isophthaloyl chloride, trimesoyl chloride, diphenyl tetracarboxylic acid chloride; and / or the organic phase solvent in the organic phase solution of the polyacyl chloride monomer comprises at least one of n-hexane, heptane, cyclohexane, Isopar G solvent; and / or the porous support membrane comprises at least one of polysulfone ultrafiltration membrane, polyethersulfone ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, polyvinylidene fluoride ultrafiltration membrane.

[0008] In an embodiment, the mass fractions of the hydroxyapatite nanoparticles, water, anionic surfactant, and polyamine monomer are 0.02-0.4, 90-110, 0.001-0.05, and 0.05-0.5, respectively.

[0009] In an embodiment, the mass percentage concentration of the organic phase solution of the polyacyl chloride monomer is 0.1-0.6%; and / or the particle size of the hydroxyapatite nanoparticles is 10-50 nanometers.

[0010] In an embodiment, the surface of the porous support membrane is sequentially immersed with the aqueous phase dispersion of the hydroxyapatite nanoparticles containing the polyamine monomer and the organic phase solution of the polyacyl chloride monomer, and a polymer is generated on the surface of the porous support membrane through the polymerization of the polyamine monomer and the polyacyl chloride monomer, comprising: pouring the aqueous phase dispersion of the hydroxyapatite nanoparticles containing the polyamine monomer on the porous support membrane, removing the aqueous phase liquid on the surface of the membrane after the initial immersion, and obtaining a pre-product membrane containing the polyamine monomer on the surface; pouring the organic phase solution of the polyacyl chloride monomer on the surface of the pre-product membrane, and generating the polymer on the surface of the porous support membrane through the polymerization of the polyamine monomer and the polyacyl chloride monomer after the secondary immersion.

[0011] In an embodiment, the polymer is used as an active separation layer, and the porous support membrane and the active separation layer are used as a nanofiltration membrane, comprising: removing the organic phase solution on the surface of the active separation layer; and using the porous support membrane and the active separation layer as the nanofiltration membrane after the drying treatment.

[0012] In an embodiment, the condition parameters of the stirring include: the stirring speed is 500-1000 revolutions per minute, and the stirring time is 10-30 minutes; and / or the condition parameters of the initial ultrasonic treatment include: the ultrasonic treatment frequency is 20-40 KHZ, and the ultrasonic treatment time is 5-15 minutes; and / or the condition of the secondary ultrasonic treatment includes: the ultrasonic treatment frequency is 25-50 KHZ, and the ultrasonic treatment time is 20-40 minutes.

[0013] In one embodiment, the initial immersion time is 2 to 10 minutes; and / or the secondary immersion time is 1 to 6 minutes; and / or the drying conditions include: a drying temperature of 40 to 60°C and a drying time of 5 to 60 minutes.

[0014] One embodiment also provides a nanofiltration membrane, which includes: a porous support membrane and an active separation layer; wherein the active separation layer is distributed on the surface of the porous support membrane.

[0015] In one embodiment, the porosity of the porous support membrane is 70-80%; and / or the pore size of the pores in the porous support membrane is 10-30 nm; and / or the thickness of the porous support membrane is 50-100 micrometers; and / or the thickness of the active separation layer is 100-300 nanometers.

[0016] One embodiment also provides an application of a nanofiltration membrane for fluoride removal.

[0017] This application presents a nanofiltration membrane with a mixed polyamide matrix, fabricated on a porous support membrane using polyamine and polyacrylamide monomers. The hydroxyapatite nanoparticles and the polyamide matrix are chemically bonded, enhancing the permeability and fluoride ion selectivity of the nanofiltration membrane while significantly improving membrane stability. Furthermore, the nanofiltration membrane prepared in this application is simple to fabricate and easily scaled up for production, making it more suitable for fluoride removal in water. Attached Figure Description

[0018] Figure 1 This is a flowchart illustrating a method for preparing a nanofiltration membrane in one embodiment. Figure 2 This is a surface morphology diagram of a nanofiltration membrane in one embodiment. Detailed Implementation

[0019] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments. Similar elements in different embodiments are referred to by associated similar element reference numerals. In the following embodiments, many details are described to facilitate a better understanding of the present application. However, those skilled in the art will readily recognize that some features may be omitted in different situations, or may be replaced by other elements, materials, or methods. In some cases, certain operations related to the present application are not shown or described in the specification. This is to avoid obscuring the core parts of the present application with excessive description. For those skilled in the art, detailed description of these related operations is not necessary; they can fully understand the related operations based on the description in the specification and general technical knowledge in the art.

[0020] Furthermore, the features, operations, or characteristics described in the specification can be combined in any suitable manner to form various embodiments. At the same time, the steps or actions in the method description can be rearranged or adjusted in a manner obvious to those skilled in the art. Therefore, the various orders in the specification and drawings are only for the clear description of a particular embodiment and do not imply a necessary order, unless otherwise stated that a particular order must be followed.

[0021] The serial numbers assigned to components in this document, such as "first" and "second," are used only to distinguish the described objects and have no sequential or technical meaning. The terms "connection" and "linkage" used in this application, unless otherwise specified, include both direct and indirect connections (linkages).

[0022] This embodiment provides a method for preparing a nanofiltration membrane, such as... Figure 1 As shown, the method includes: S1. The surface of the porous support membrane is sequentially impregnated with an aqueous dispersion of hydroxyapatite nanoparticles containing polyamine monomers and an organic phase solution of polyacrylamide monomers. Polymers are generated on the surface of the porous support membrane through the polymerization reaction of polyamine monomers and polyacrylamide monomers. S2. The polymer is used as the active separation layer, and the porous support membrane and the active separation layer are used as nanofiltration membranes.

[0023] This application presents a nanofiltration membrane with a mixed polyamide matrix, fabricated on a porous support membrane using polyamine and polyacrylamide monomers. The introduction of hydroxyapatite nanoparticles into the polyamide mixed matrix nanofiltration membrane construction facilitates membrane interface engineering and optimizes the membrane structure. During operation, the confinement effect generated by the nanoscale pore size of the membrane, combined with the selective adsorption force of hydroxyapatite, restricts the diffusion and transfer of fluoride ions within the membrane, thereby enhancing fluoride ion retention and maintaining good stability during long-term operation.

[0024] Step S1 specifically includes the following steps: S11. Add hydroxyapatite nanoparticles to water and stir to obtain an aqueous solution of hydroxyapatite nanoparticles. S12. An anionic surfactant is added to an aqueous solution of hydroxyapatite nanoparticles, and the ultrasonically treated solution is obtained by initial ultrasonic treatment. S13. Add polyamine monomer to the ultrasonically treated solution, and obtain an aqueous dispersion of hydroxyapatite nanoparticles after a second ultrasonic treatment. S14. Pour the aqueous dispersion of hydroxyapatite nanoparticles containing polyamine monomers onto a porous support membrane. After the initial immersion, remove the aqueous liquid from the membrane surface to obtain a pre-finished membrane containing polyamine monomers on the surface. S15. Pour the organic phase solution of polyacrylamide chloride monomers onto the surface of the pre-finished membrane. After a second impregnation, the polymerization reaction of polyamine monomers and polyacrylamide chloride monomers generates polymers on the surface of the porous support membrane.

[0025] The anionic surfactant includes at least one of the following: sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium stearate, sodium polyvinyl sulfonate, and sodium laurate.

[0026] Anionic surfactants can significantly improve the homogeneity of hydroxyapatite in solution and its uniform distribution on the membrane by altering the interfacial tension and surface properties of the aqueous solution. The principle is as follows: the negatively charged groups of the anionic surfactant adsorb onto the positively charged sites (Ca²⁺) of hydroxyapatite (HAP) through electrostatic interactions. The hydrophobic long chains (hydrocarbon chains) of the surfactant molecules adsorbed on the HAP surface extend into the surrounding aqueous solution. When two HAP particles approach each other, these extended hydrophobic chains overlap and compress, generating a steric hindrance effect that promotes HAP dispersion. Furthermore, since subsequent polymerization reactions often occur at the interface between two liquid phases, the anionic surfactant can also reduce interfacial tension, helping reactants to distribute more uniformly at the interface, reducing uneven aggregation of reactants, and preventing irregular structures or defects on the membrane surface.

[0027] The polyamine monomers include at least one of the following: piperazine, m-phenylenediamine, N-aminoethylpiperazine, and p-phenylenediamine.

[0028] The subsequent interfacial polymerization reaction in this scheme is a rapid polycondensation reaction between amines and acyl chlorides. These polyamine monomers all have highly reactive amine groups. For example, m-phenylenediamine has two highly reactive amine functional groups (-NH2), each piperazine molecule contains two reactive sites (NH on a secondary amine), N-aminoethylpiperazine has both a secondary amine group like piperazine and a primary amine group like MPD, and p-phenylenediamine and m-phenylenediamine are both aromatic diamines, except that their two amine groups are located at the para position on the benzene ring.

[0029] The mass fractions of hydroxyapatite nanoparticles, water, anionic surfactant, and polyamine monomer are 0.02–0.4, 90–110, 0.001–0.05, and 0.05–0.5, respectively.

[0030] This method uses the minimum amount of hydroxyapatite nanoparticles to form an aqueous dispersion containing polyamine monomers, while simultaneously achieving better solubility and content requirements.

[0031] Specifically, the mass fraction of hydroxyapatite nanoparticles can be 0.05, 0.1, 0.15, 0.2, 0.25, or 0.35 parts; the mass fraction of water can be 95, 100, or 105 parts; the mass fraction of anionic surfactant can be 0.005, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, or 0.045 parts; and the mass fraction of polyamine monomer can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, or 0.45 parts.

[0032] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or thresholds should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0033] The stirring conditions include: a stirring speed of 500-1000 rpm and a stirring time of 10-30 minutes.

[0034] Because dry hydroxyapatite nanoparticle powder has extremely high surface energy, it forms large, visible agglomerates containing air. Stirring first provides shear force, breaking these agglomerates into smaller particles. Simultaneously, stirring ensures sufficient contact between the hydroxyapatite and water, helping water molecules penetrate into the gaps between the powder particles, replacing the air and achieving initial "wetting." If the powder is not fully wetted, surfactants cannot effectively contact and adsorb onto the particle surface; therefore, stirring also rapidly and uniformly disperses subsequently added anionic surfactants throughout the aqueous system.

[0035] Specifically, the stirring speed in the stirring conditions can be 600, 700, 800, or 900 rpm, and the stirring time can be 15, 20, or 25 minutes.

[0036] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or thresholds should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0037] The initial ultrasound treatment parameters include: ultrasound frequency of 20–40 kHz and ultrasound time of 5–15 minutes.

[0038] The initial ultrasonic treatment generates extremely localized energy through cavitation. Ultrasonic waves create countless tiny vacuum bubbles in the liquid, causing them to collapse violently and instantaneously, generating extremely strong shock waves and microjets. This immense localized force can directly impact and break down the binding points between nanoparticles, thus decomposing aggregates into individual nanoparticles. Therefore, this initial ultrasonic treatment can accelerate the adsorption process of anionic surfactant molecules on the hydroxyapatite surface and help it form a more complete and ordered coating layer, thereby achieving more effective surface charge modification and steric hindrance protection, preventing particle re-aggregation.

[0039] Specifically, the ultrasonic frequency in the initial ultrasonic treatment can be 25, 30, or 35 kHz, and the ultrasonic time can be 8, 10, 12, or 14 minutes.

[0040] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or thresholds should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0041] The conditions for secondary ultrasound include: an ultrasound frequency of 25–50 kHz and an ultrasound duration of 20–40 minutes. The role of secondary ultrasonic treatment is "functionalization" rather than "dispersion." Through the activation effect of ultrasonic energy, efficient and uniform adsorption and enrichment of polyamine monomers on the surface of hydroxyapatite nanoparticles are achieved, preparing for the preparation of high-performance, structurally uniform nanocomposite separation membranes. Secondary ultrasonic treatment transforms hydroxyapatite from an inorganic filler into an active platform rich in amine reaction sites. These surface-enriched amine molecules can directly participate in the polymerization reaction of acyl chlorides. Through the adsorption and other effects promoted by secondary ultrasound, the interaction between hydroxyapatite and the polyamide network is no longer a weak physical interaction, but a strong electrostatic, coordination, and even covalent bond. This greatly improves the compatibility and binding force between inorganic nanoparticles and organic polymers, avoids interfacial defects, and allows hydroxyapatite to play a more effective role.

[0042] Specifically, the ultrasonic frequency in the secondary ultrasonic treatment can be 30, 35, 40, or 45 kHz, and the ultrasonic time can be 25, 30, or 35 minutes.

[0043] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or thresholds should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0044] The porous support membrane includes at least one of the following: polysulfone ultrafiltration membrane, polyethersulfone ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, and polyvinylidene fluoride ultrafiltration membrane.

[0045] The polyamide film prepared by this invention is very thin (typically several hundred nanometers) and fragile, making it impossible to form and use independently. Therefore, polysulfone (PSF), polyethersulfone (PES), polyacrylonitrile (PAN), and polyvinylidene fluoride (PVDF) are selected as the base membrane materials because they can provide support on a porous ultrafiltration (UF) base membrane with high mechanical strength and good chemical stability.

[0046] The initial soaking time is 2 to 10 minutes.

[0047] The initial impregnation parameters not only provide sufficient time for the amine monomers to diffuse and adsorb into the pores of the base membrane, but also allow the hydroxyapatite nanoparticles to better reside in the pores and surface of the membrane during impregnation. After pouring the aqueous phase of the amine monomers, a liquid layer forms on the surface of the base membrane. During this time, the liquid reaches an equilibrium state due to surface tension, forming a film of uniform thickness. This eliminates the unevenness in liquid layer thickness that may be caused by the pouring operation, preparing for the subsequent formation of a uniform polyamide layer. Through the initial impregnation treatment, the amine monomers participating in the interfacial polymerization reaction no longer come only from the surface aqueous solution, but from the entire base membrane surface saturated with amine monomers. When the oil phase is poured in, the acyl chloride monomers, in addition to reacting with the amines on the surface, can diffuse into the surface pores of the base membrane and react with the amine monomers adsorbed in the pores. The hydroxyapatite nanoparticles loaded with amine monomers also participate in interfacial polymerization, and the polyamide network encapsulates and firmly fixes them to the membrane. This enhances the bonding force between the polyamide separation layer and the porous support layer, effectively preventing delamination between the two layers under high-pressure operating conditions. Specifically, the initial soaking time is 4, 5, 7, or 9 minutes.

[0048] The second soaking time is 1 to 6 minutes.

[0049] The secondary impregnation parameters are set to facilitate immediate contact between the acyl chloride oil phase and the polyamine monomers adsorbed on the membrane surface and in the shallow pores. Since amine monomers are insoluble in the organic phase and acyl chloride monomers are insoluble in the aqueous phase, this highly reactive polycondensation reaction is strictly confined to the interface between the aqueous and organic phases. This interfacial polymerization reaction initiated by the secondary impregnation generates a polyamide active separation layer at a precise location, resulting in a higher quality polyamide layer. Simultaneously, it allows hydroxyapatite nanoparticles to be incorporated into the polyamide network, thereby enhancing the fluoride ion selectivity of the nanofiltration membrane. Specifically, the secondary impregnation times are 2, 3, 4, and 5 minutes.

[0050] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or thresholds should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0051] The polyacryl chloride monomer in the organic phase solution includes at least one of the following: isophthaloyl chloride, trimesoyl chloride, and biphenyltetracarboxylate chloride.

[0052] The subsequent interfacial polymerization reaction in this scheme is a rapid polycondensation reaction between amines and acyl chlorides. All three polyacyl chloride monomers are aromatic acyl chlorides, which impart rigidity and chemical stability to the resulting polyamide chains.

[0053] The mass percentage concentration of polyacrylamide chloride monomer in the organic phase solution is 0.1% to 0.6%.

[0054] Since interfacial polymerization is a diffusion-controlled reaction, acyl chloride monomers need to diffuse from the organic phase to the interface to participate in the reaction. This concentration maintains a good reaction rate and interfacial stability. At this concentration, polyacyl chloride monomers can react fully with amine monomers to form a polyamide layer with high crosslinking degree and dense network structure.

[0055] Specifically, the mass percentage concentration of polyamine monomers in the organic phase solution of polyacrylamide chloride monomers can be 0.2, 0.3, 0.4, or 0.5%.

[0056] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or thresholds should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0057] The organic solvent in the organic phase solution of the polyacrylamide chloride monomer is n-hexane, heptane, cyclohexane, or Isopar G solvent.

[0058] The selected solvent must be able to fully dissolve the acyl chloride monomer to form a sufficiently concentrated oil phase solution, ensuring that enough monomers diffuse rapidly to the interface to participate in the reaction. The choice of hexane, heptane, cyclohexane, or Isopar G as solvent is based on a fundamental principle: it must be able to dissolve the reactant (acyl chloride), but at the same time be completely incompatible with the other reactant (amine) and its phase (water).

[0059] Step S2 specifically includes the following steps: S21. Remove the organic phase solution from the surface of the active separation layer; S22. After drying, the porous support membrane and the active separation layer are used as nanofiltration membranes.

[0060] The drying conditions include: drying temperature of 40–60℃ and drying time of 5–60 minutes.

[0061] This drying temperature provides energy to promote further cross-linking of unreacted groups in the polyamide layer, while gently removing residual solvent, thus stabilizing the membrane structure. Therefore, the drying process effectively increases the actual cross-linking density of the polyamide network by promoting the reaction of residual functional groups. A higher cross-linking density in the polyamide network means greater rigidity, which strengthens the mechanical properties of the nanofiltration membrane and makes it more suitable for long-term operation under high pressure.

[0062] Specifically, the drying temperature in the drying process can be 45, 50, or 55℃, and the drying time can be 10, 15, 20, 25, 30, 35, 40, 45, 50, or 55 minutes.

[0063] This embodiment provides a nanofiltration membrane, such as Figure 1 The image shown depicts the surface morphology of the nanofiltration membrane. The nanofiltration membrane comprises a porous support membrane and an active separation layer; the active separation layer is distributed on the surface of the porous support membrane.

[0064] The porous support membrane has a porosity of 70-80%; and / or the pore size of the porous support membrane is 10-30 nm; and / or the thickness of the porous support membrane is 50-100 micrometers; and / or the thickness of the active separation layer is 100-300 nanometers.

[0065] Porous support membranes provide robust and low-resistance physical support for the active separation layer. If the membrane is too thin, it is easily damaged and cannot withstand the operating pressure. If it is too thick, the water flow resistance is large, which significantly reduces the overall water flux of the membrane. However, at this thickness, the porous support membrane can maintain a balance between mechanical strength and mass transfer resistance.

[0066] The thickness of the active separation layer greatly reduces water transport resistance, ensuring high throughput, while also being sufficient to form a complete and dense cross-linked network, providing high selectivity.

[0067] Specifically, the thickness of the porous support layer is 60, 70, 80, 90 micrometers or any specific value within the above range; and / or, the thickness of the active separation layer is 150, 200, 250 nanometers or any specific value within the above range.

[0068] The nanofiltration membrane in this embodiment has increased confinement force compared to conventional nanofiltration membranes for fluoride removal, resulting in a higher fluoride ion rejection rate and a certain rejection rate for other ions. It is especially suitable for the efficient removal of monovalent fluoride ions from water.

[0069] To better explain this application, embodiments and comparative examples are also provided below.

[0070] Example 1 0.02 g of hydroxyapatite nanoparticles were added to 100 g of deionized water and stirred at 500 rpm for 30 minutes until homogeneous. Then, 0.001 g of sodium dodecyl sulfate was added, followed by sonication at 20 kHz for 15 minutes. Next, 0.05 g of piperazine was added to the above solution, and the mixture was sonicated at 25 kHz for 40 minutes to form an aqueous dispersion of hydroxyapatite nanoparticles. The above-prepared aqueous dispersion was poured onto a polysulfone porous ultrafiltration membrane and immersed for 2 minutes. Then, the aqueous liquid on the membrane surface was removed. Next, a solution containing 0.1 wt% trimesoyl chloride in n-hexane was poured onto the membrane surface and immersed for 1 minute. Then, the organic phase solution on the membrane surface was removed. After drying at 40 °C for 60 minutes, the resulting membrane was immersed and washed in deionized water to obtain a hydroxyapatite mixed matrix nanofiltration membrane.

[0071] Example 2 0.4 g of hydroxyapatite nanoparticles were added to 100 g of deionized water and stirred at 1000 rpm for 10 minutes until homogeneous. Then, 0.05 g of sodium dodecyl sulfate was added, followed by sonication at 40 kHz for 5 minutes. Next, 0.5 g of piperazine was added to the above solution, and the mixture was sonicated at 50 kHz for 20 minutes to form an aqueous dispersion of hydroxyapatite nanoparticles. The above-prepared aqueous dispersion was poured onto a polysulfone porous ultrafiltration membrane and immersed for 10 minutes. Then, the aqueous liquid on the membrane surface was removed. Next, a solution containing 0.6 wt% trimesoyl chloride in n-hexane was poured onto the membrane surface and immersed for 6 minutes. Then, the organic phase solution on the membrane surface was removed. After drying at 60 °C for 5 minutes, the resulting membrane was immersed and washed in deionized water to obtain a hydroxyapatite mixed matrix nanofiltration membrane.

[0072] Example 3 0.2 g of hydroxyapatite nanoparticles were added to 100 g of deionized water and stirred at 800 rpm for 20 minutes until homogeneous. Then, 0.01 g of sodium dodecyl sulfate was added, followed by sonication at 30 kHz for 10 minutes. Next, 0.2 g of piperazine was added to the above solution, and the mixture was sonicated at 35 kHz for 30 minutes to form an aqueous dispersion of hydroxyapatite nanoparticles. The above-prepared aqueous dispersion was poured onto a polysulfone porous ultrafiltration membrane and immersed for 5 minutes. Then, the aqueous liquid on the membrane surface was removed. Next, a solution containing 0.3 wt% trimesoyl chloride in n-hexane was poured onto the membrane surface and immersed for 2 minutes. Then, the organic phase solution on the membrane surface was removed. After drying at 50 °C for 20 minutes, the resulting membrane was immersed and washed in deionized water to obtain a hydroxyapatite mixed matrix nanofiltration membrane.

[0073] Example 4 0.2 g of hydroxyapatite nanoparticles were added to 100 g of deionized water and stirred at 600 rpm for 15 minutes until homogeneous. Then, 0.02 g of sodium dodecyl sulfate was added, followed by sonication at 25 kHz for 10 minutes. Next, 0.25 g of piperazine was added to the above solution, and the mixture was sonicated at 45 kHz for 32 minutes to form an aqueous dispersion of hydroxyapatite nanoparticles. The above-prepared aqueous dispersion was poured onto a polyacrylonitrile porous ultrafiltration membrane and immersed for 5 minutes. Then, the aqueous liquid on the membrane surface was removed. Next, a solution containing 0.35 wt% trimesoyl chloride in n-hexane was poured onto the membrane surface and immersed for 3 minutes. Then, the organic phase solution on the membrane surface was removed. After drying at 45 °C for 20 minutes, the resulting membrane was immersed and washed in deionized water to obtain a hydroxyapatite mixed matrix nanofiltration membrane.

[0074] Example 5 0.15 g of hydroxyapatite nanoparticles were added to 100 g of deionized water and stirred at 700 rpm for 15 minutes until homogeneous. Then, 0.02 g of sodium lauryl precipitate was added, followed by sonication at 20 kHz for 10 minutes. Next, 0.25 g of piperazine was added to the above solution, and the mixture was sonicated at 40 kHz for 35 minutes to form an aqueous dispersion of hydroxyapatite nanoparticles. The above-prepared aqueous dispersion was poured onto a polyacrylonitrile porous ultrafiltration membrane and immersed for 2 minutes. Then, the aqueous liquid on the membrane surface was removed. Next, a solution containing 0.25 wt% trimesoyl chloride in n-hexane was poured onto the membrane surface and immersed for 3 minutes. Then, the organic phase solution on the membrane surface was removed. After drying at 55 °C for 20 minutes, the resulting membrane was immersed and washed in deionized water to obtain a hydroxyapatite mixed matrix nanofiltration membrane.

[0075] Example 6 0.35 g of hydroxyapatite nanoparticles were added to 100 g of deionized water and stirred at 600 rpm for 15 minutes until homogeneous. Then, 0.02 g of sodium dodecylbenzenesulfonate was added, followed by ultrasonic treatment at 30 kHz for 12 minutes. Next, 0.25 g of p-phenylenediamine was added to the above solution, and ultrasonic treatment at 25 kHz for 30 minutes was performed to form an aqueous dispersion of hydroxyapatite nanoparticles. The above-prepared aqueous dispersion was poured onto a polyethersulfone porous ultrafiltration membrane and immersed for 3 minutes. Then, the aqueous liquid on the membrane surface was removed. Next, a solution containing 0.25 wt% trimesoyl chloride in n-hexane was poured onto the membrane surface and immersed for 4 minutes. Then, the organic phase solution on the membrane surface was removed. After drying at 45 °C for 30 minutes, the resulting membrane was immersed and washed in deionized water to obtain a hydroxyapatite mixed matrix nanofiltration membrane.

[0076] Example 7 0.28 g of hydroxyapatite nanoparticles were added to 100 g of deionized water and stirred at 650 rpm for 10 minutes until homogeneous. Then, 0.015 g of sodium dodecylbenzenesulfonate was added, followed by ultrasonic treatment at 30 kHz for 10 minutes. Next, 0.21 g of p-phenylenediamine was added to the above solution, and ultrasonic treatment at 35 kHz for 35 minutes was performed to form an aqueous dispersion of hydroxyapatite nanoparticles. The above-prepared aqueous dispersion was poured onto a polyethersulfone porous ultrafiltration membrane and immersed for 3 minutes. Then, the aqueous liquid on the membrane surface was removed. Next, a solution containing 0.25 wt% isophthaloyl chloride in n-hexane was poured onto the membrane surface and immersed for 5 minutes. Then, the organic phase solution on the membrane surface was removed. After drying at 45 °C for 10 minutes, the resulting membrane was immersed and washed in deionized water to obtain a hydroxyapatite mixed matrix nanofiltration membrane.

[0077] Example 8 0.38 g of hydroxyapatite nanoparticles were added to 100 g of deionized water and stirred at 680 rpm for 15 minutes until homogeneous. Then, 0.029 g of sodium dodecylbenzenesulfonate was added, followed by ultrasonic treatment at 30 kHz for 15 minutes. Next, 0.30 g of m-phenylenediamine was added to the above solution, and ultrasonic treatment at 35 kHz for 30 minutes was performed to form an aqueous dispersion of hydroxyapatite nanoparticles. The above-prepared aqueous dispersion was poured onto a polyethersulfone porous ultrafiltration membrane and immersed for 8 minutes. Then, the aqueous liquid on the membrane surface was removed. Next, a cyclohexane solution containing 0.25 wt% biphenyltetramethylchlorohydrin was poured onto the membrane surface and immersed for 5 minutes. Then, the organic phase solution on the membrane surface was removed. After drying at 55 °C for 20 minutes, the resulting membrane was immersed and washed in deionized water to obtain a hydroxyapatite mixed matrix nanofiltration membrane.

[0078] Comparative Example 1 The difference from the steps in Example 3 is that hydroxyapatite nanoparticles were not introduced into the membrane, and the polyamide nanofiltration membrane was prepared directly using piperazine and pyromellitic trimethylol chloride as raw materials.

[0079] Comparative Example 2 The difference from the steps in Example 3 is that piperazine is not added to the aqueous phase, and the cross-linked membrane is prepared directly using hydroxyapatite nanoparticles and trimesoyl chloride as raw materials.

[0080] Comparative Example 3 The difference from the steps in Example 3 is that nano-silica is used instead of hydroxyapatite nanoparticles in the preparation of polyamide nanofiltration membranes.

[0081] The fluoride ion separation performance of the filter membranes prepared in the above embodiments and comparative examples was tested (e.g., filtering a 10 ppm sodium fluoride solution). The test method for fluoride ion separation performance is as follows: The prepared membrane was placed in a conventional nanofiltration test apparatus. Before testing, the membrane was pre-pressurized at an operating pressure of 0.6 MPa for 1 h. Then, under test conditions of 25℃ and 0.6 MPa, the water permeate flux (J) and fluoride ion rejection rate (R) of the membrane were measured. The calculation formulas are: J=V / (At); R=1-Cp⁄Cf; where V is the volume of feed liquid permeating through the membrane, and A is the effective area of ​​the membrane, which is 22.4 cm². 2 t represents the running time, Cp represents the fluoride ion concentration in the permeate measured by the fluoride ion detection electrode, and Cf represents the fluoride ion concentration in the feed solution measured by the fluoride ion detection electrode. The test results are shown in Table 1 below.

[0082] Table 1. Data from fluoride ion separation performance tests.

[0083] According to the data in the table, in Comparative Example 1, both the water flux and sodium fluoride rejection rate were lower than in Example 3. This is because the membrane in Comparative Example 1 is cross-linked from a single rigid polyamide polymer chain, resulting in a denser molecular structure and thus a lower water flux. Furthermore, since this membrane primarily relies on pore size sieving to remove fluoride ions, it lacks confinement forces, leading to a lower fluoride rejection rate typical of conventional nanofiltration membranes. In Comparative Example 2, no piperazine was added to the aqueous phase; instead, a cross-linked membrane was prepared directly from hydroxyapatite nanoparticles and trimesoyl chloride. Compared to Example 3, the water flux was higher, but the sodium fluoride rejection rate was very low. This is because the absence of piperazine prevents the polymerization reaction between amine groups and acyl chloride, failing to form a complete active separation layer. Consequently, the confinement effect formed by nanoscale channels cannot be utilized to enhance fluoride removal. The limited rejection rate relies mainly on the temporary adsorption of hydroxyapatite, and after long-term operation, the rejection rate will further decrease to below 1%. The high water flux is due to the lack of a complete separation layer, so the data primarily reflects the water flux of the ultrafiltration membrane. This comparative example, however, cannot meet the defluorination requirements due to its extremely low rejection rate. In Comparative Example 3, nano-silica was added to the aqueous phase. Compared to Example 3, both the water flux and sodium fluoride rejection rate were lower. This is because nano-silica, as an inorganic nanomaterial, has poor compatibility with the polyamide matrix formed by interfacial polymerization, lacks covalent bonds, and is prone to forming membrane defects, resulting in low flux. Furthermore, the membrane's hydrophilicity is lower than that of Example 3, leading to even lower flux.

[0084] In the above embodiments, an anionic surfactant was added to an aqueous solution of hydroxyapatite nanoparticles and sonicated. Then, a polyamine monomer was added to the aqueous dispersion to form an aqueous phase solution. Subsequently, a nanofiltration membrane was prepared on a porous support membrane using interfacial polymerization. This method optimizes the crosslinking structure and chemical properties of the membrane interfacial separation layer by controlling the interfacial polymerization process and the dispersion state of hydroxyapatite within the membrane, thus constructing a mixed-matrix nanofiltration membrane with specifically enhanced fluoride removal performance. The resulting nanofiltration membrane exhibits good hydrophilic stability. The hydroxyapatite introduced into the membrane can generate adsorption and ion exchange forces for fluoride ions, regulating the transport process of fluoride ions in the confined membrane pores, increasing the permeation resistance of fluoride ions in the feed solution, and achieving efficient separation of fluoride ions with a good retention rate. As shown in the data of the examples in the table, the water permeate flux of this nanofiltration membrane is higher than 45.0 L•m at an operating pressure of 0.6 MPa. -2 •h -1 The rejection rate for monovalent fluoride ions is as high as 65.0% or more.

[0085] Finally, it should be noted that in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes the element.

[0086] The above examples illustrate the present invention only to aid in understanding it and are not intended to limit the scope of the invention. Those skilled in the art can make various simple deductions, modifications, or substitutions based on the principles of this invention.

Claims

1. A method for preparing a nanofiltration membrane, characterized in that, The method includes: The surface of a porous support membrane is sequentially impregnated with an aqueous dispersion of hydroxyapatite nanoparticles containing polyamine monomers and an organic solution of polyacrylamide monomers, and a polymer is generated on the surface of the porous support membrane through the polymerization reaction of polyamine monomers and polyacrylamide monomers. The polymer is used as the active separation layer, and the porous support membrane and the active separation layer are used as nanofiltration membranes.

2. The method according to claim 1, characterized in that, An aqueous dispersion of hydroxyapatite nanoparticles containing polyamine monomers was obtained, comprising: Hydroxyapatite nanoparticles were added to water, and an aqueous solution of hydroxyapatite nanoparticles was obtained by stirring. An anionic surfactant was added to the aqueous solution of the hydroxyapatite nanoparticles, and the ultrasonically treated solution was obtained by initial ultrasonic treatment. A polyamine monomer was added to the ultrasonically treated solution, and a hydroxyapatite nanoparticle aqueous dispersion was obtained after a second ultrasonic treatment.

3. The method according to claim 2, characterized in that, The anionic surfactant comprises at least one of the following: sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium stearate, sodium polyvinyl sulfonate, sodium laurate; and / or The polyamine monomer comprises at least one of the following: piperazine, m-phenylenediamine, N-aminoethylpiperazine, p-phenylenediamine; and / or The polyacryl chloride monomer in the organic phase solution comprises at least one of the following: isophthaloyl chloride, trimesoyl pyromellitic chloride, biphenyltetracarboxylic chloride; and / or The organic solvent in the polyacrylamide chloride monomer organic phase solution includes at least one of the following: n-hexane, heptane, cyclohexane, Isopar G solvent; and / or The porous support membrane includes at least one of the following: polysulfone ultrafiltration membrane, polyethersulfone ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, and polyvinylidene fluoride ultrafiltration membrane.

4. The method according to claim 2, characterized in that, The hydroxyapatite nanoparticles, the water, the anionic surfactant, and the polyamine monomer are present in mass fractions of 0.02–0.4, 90–110, 0.001–0.05, and 0.05–0.5, respectively; and / or The mass percentage concentration of the polyacrylamide chloride monomer organic phase solution is 0.1–0.6%; and / or The hydroxyapatite nanoparticles have a particle size of 10-50 nanometers.

5. The method according to claim 2, characterized in that, The surface of a porous support membrane is sequentially impregnated with an aqueous dispersion of hydroxyapatite nanoparticles containing polyamine monomers and an organic solution of polyacrylamide chloride monomers. A polymer is then generated on the surface of the porous support membrane through a polymerization reaction of the polyamine monomers and polyacrylamide chloride monomers, comprising: The aqueous dispersion of hydroxyapatite nanoparticles containing polyamine monomers is poured onto the porous support membrane. After the initial immersion, the aqueous liquid on the membrane surface is removed to obtain a pre-finished membrane containing polyamine monomers on the surface. The organic phase solution of the polyacrylamide chloride monomer is poured onto the surface of the pre-finished membrane. After a second impregnation, the polymerization reaction of the polyamine monomer and the polyacrylamide chloride monomer generates a polymer on the surface of the porous support membrane.

6. The method according to claim 5, characterized in that, Using the polymer as an active separation layer, and the porous support membrane and the active separation layer as a nanofiltration membrane, the method comprises: Remove the organic phase solution from the surface of the active separation layer; After drying, the porous support membrane and the active separation layer are used as nanofiltration membranes.

7. The method according to claim 2, characterized in that, The stirring conditions include: a stirring speed of 500–1000 rpm and a stirring time of 10–30 minutes; and / or The initial ultrasonic treatment parameters include: an ultrasonic treatment frequency of 20–40 kHz and an ultrasonic treatment time of 5–15 minutes; and / or The conditions for the secondary ultrasonic treatment include: an ultrasonic treatment frequency of 25–50 kHz and an ultrasonic treatment time of 20–40 minutes.

8. The method according to claim 6, characterized in that, The initial immersion time is 2 to 10 minutes; and / or The secondary immersion time is 1 to 6 minutes; and / or The drying conditions include: a drying temperature of 40–60°C and a drying time of 5–60 minutes.

9. A nanofiltration membrane, characterized in that, The nanofiltration membrane comprises: a porous support membrane and an active separation layer; the active separation layer is distributed on the surface of the porous support membrane; The porous support membrane has a porosity of 70-80%; the pore size of the porous support membrane is 10-30 nm; the thickness of the porous support membrane is 50-100 μm; and the thickness of the active separation layer is 100-300 nm.

10. The application of nanofiltration membranes, characterized in that, The nanofiltration membrane is used for fluoride removal.